Problems of Interaction Between Judicial Authorities - Teremetskyi, Vladyslav (Actual problems of law (Aktual'ni problemi pravoznavstva), 2022)
The implementation of the judicial reform from the time of the declaration of Ukraine’s independence until present period of time has been determined by the global tendencies of Ukraine’s integration into the EU and the world community, by the improvement of legislation in accordance with European and international standards, as well as by the construction of an effective and independent judicial system. It has been substantiated that the key principles in the system of checks and balances are interaction, interdependence, mutual control and mutual penetration. It has been emphasized that issues of the interaction between judicial authorities and subjects of the legislative initiative is of great importance taking into account the special place and role of such authorities. Analysis of the current legislation demonstrates that such interaction primarily takes place in the law-making process. It has been proved that the effectiveness of applying mandatory advisory conclusions of the High Council of Justice is currently the most relevant issue. It has been established that the parliament often does not take into account the recommendations of the High Council of Justice contained in its conclusions, which leads to a long-term process of declaring certain provisions of laws as unconstitutional ones. It has been stated that it is necessary to amend the Regulations of the Verkhovna Rada of Ukraine and the High Council of Justice in order to improve the mechanism of interaction between them. Those Regulations should establish the provisions on the results of the parliament’s consideration of mandatory advisory conclusions and acts of response – notification about the results of consideration and the reasons for applying (or not applying) the recommendations outlined in the conclusions. Besides, the High Council of Justice can be effectively involved in the examination of draft laws on the formation, reorganization or liquidation of courts, the judicial system and the status of judges, as well as the creation of a special agency.